CONGLOMERATE ROCKS "BRECCIA VERDE ANTICA" ARCHAEOLOGY, PETROLOGY, DETERIORATION AND TECHNOLOGY OF QUARRYING AT HAMMAMAT QUARRIES IN THE EASTEREN DESERT. - dr.HESHAM ABBAS KMALLY (Journal of General Union of Arab Archaeologists, 2010)
One of the most interesting of the monumental rocks of Egypt is the green conglomerates of the Hammamat valley which was used for bowls, vessels, sarcophagus and other objects, from a very early period. The quarries of wadi Hammamat produced the green ornamental stone known in Roman period as "Breccia verde antica". Generally the ancient conglomerate was used occasionally in Egypt at pharaonic time and late period, but it was quarried chiefly by the Roman for export to Italy. The conglomerate rocks range from coarse to fine conglomerates. They are composed of great assortment of rock fragments such as meta-sediments, meta-volcanic and granites. Some pebbles of the coarse conglomerates are previously deposited conglomerates. Pollution, humidity or moisture, solar radiation, rainfall and groundwater represent important factors for disintegration of green conglomerate rocks. Many types of destruction have been noted such as micro-cracks, fractures, joints, exfoliation, crumbling, discoloration, leaching and staining with iron oxides. The conglomerate rock sometimes changes into fragmented, soft residual and parent matter of the soil. Moreover, individual grains of feldspar and quartz begin to become loosened and the rock shows superficial granular disintegration due to, growth of salts and physiochemical weathering